Effect of Boron powder purity on superconducting properties of bulk MgB2 - Xu, Xun; dos Santos, Dayse I. [UNESP]; Kim, J. H.; Yeoh, W. K.; Qin, M. J.; Konstantinov, K.; Dou, S. X. (Elsevier, 2007)
In order to study the influence of the amorphous Boron powder on the superconducting properties, MgB2 bulk samples were prepared using 96% and 99% pure commercial Boron powder as well as 92% commercial Boron powder after purification process. The results showed that the original 96% and the purified 92% powders have larger particle size compared to the pure 99% Boron powder, which leads to reduce magnetic critical current densities. In order to get higher performance MgB2, the purified low grade Boron powder need further control of their microstructure such as smaller particle size to enhance flux pinning from the grain boundaries which represent effective pinning centers. © 2007 Elsevier B.V. All rights reserved.
Keywords: Critical current density; Flux pinning; MgB2; Particle size effect; Boron; Current density; Microstructure; Purification; Powder metals